2011
DOI: 10.1007/s12185-010-0750-2
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and prognosis in patients with chronic lymphocytic leukaemia

Abstract: In the present study, telomere length, telomerase activity, the mutation load of immunoglobulin variable heavy chain (IGHV) genes, and established prognostic factors were investigated in 78 patients with chronic lymphocytic leukaemia (CLL) to determine the impact of telomere biology on the pathogenesis of CLL. Telomere length was measured by an automated multi-colour flow-FISH, and an age-independent delta telomere length (ΔTL) was calculated. CLL with unmutated IGHV genes was associated with shorter telomeres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
4
26
0
1
Order By: Relevance
“…In agreement with the aforementioned study [15], treatment did not seem to have any effect on TL and there was no correlation between TL and need for therapy. Notably, TL in follow-up samples was significantly associated with overall survival (P 5 0.006, not shown in figure) indicating that TL can also be used for prognostication in CLL when analyzed at later time-points during the course of disease.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…In agreement with the aforementioned study [15], treatment did not seem to have any effect on TL and there was no correlation between TL and need for therapy. Notably, TL in follow-up samples was significantly associated with overall survival (P 5 0.006, not shown in figure) indicating that TL can also be used for prognostication in CLL when analyzed at later time-points during the course of disease.…”
Section: Introductionsupporting
confidence: 89%
“…The future status of these biomarkers as a basis for clinical decision makings has not yet been fully defined, although the immunoglobulin heavy chain variable (IGHV) gene mutational status and in particular the presence of certain recurrent genomic aberrations (i.e., 11q2, 112, 13q2, 17p2) are commonly applied biomarkers [5][6][7]. Several studies have lately indicated TL as a potential prognostic marker in CLL, whereby short telomeres may predict poor clinical outcome [8][9][10][11][12][13][14][15]. Furthermore, a strong association has been reported between short TL and IGHV-unmutated CLL [11], and high-risk genomic aberrations such as del(17p) [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CLL lymphocytes are characterized by shorter telomeres and higher telomerase activity than normal B lymphocytes, what indicates on a greater number of their divisions in the past (Damle et al, 2004). Additionally, shorter telomeres are associated with genetic aberrations of defavourable prognostic signification, mainly unmutated status of the immunoglobulin heavy chain variable gene (Roos et al, 2008), and correlate with shorter progression-free and overall survival of CLL patients (Sellmann et al, 2011). These observations lead to a possible conclusion, that shorter lymphocyte doubling time -well known marker of the aggressive course of the disease -results from higher proliferation rate of neoplastic cells.…”
Section: Telomeres Length and Dna Synthesis In Vivomentioning
confidence: 99%